2019
DOI: 10.2743/jve.23.104
|View full text |Cite
|
Sign up to set email alerts
|

Survey of Zoonotic Pathogens in Dogs and CatsCoordinating with Public Animal Shelter in Niigata Prefecture, Japan

Abstract: This study aimed to investigate the recent prevalence of intestinal parasites and enteric bacterial pathogen (diarrheagenic Escherichia coli, Salmonella sp., Yersinia sp., Campylobacter sp.) in companion animals in Niigata Prefecture, Japan. From May to December each of 2015 and 2016, fecal samples were collected from 136 dogs and 176 cats in Niigata public animal shelters and were examined parasitologically and bacteriologically in Niigata prefectural institute of public health and environmental sciences. Ove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…The infestation due to adult worms is asymptomatic in most cases; however, anorexia, diarrhea, and malnutrition are occasionally observed in companion animals, and intestinal obstruction may be caused in more severe infections [12]. Extensive studies of Spirometra infections have been performed in companion animals and wildlife in Japan and the etiological agents have been identified as Spirometra erinacei [1,16] or Spirometra erinaceieuropaei [3][4][5]7,11,[13][14][15]17,[18][19][20][21] based on the morphology of adult worms and eggs found. Molecular studies have recently revealed that two other species, Spirometra mansoni and Spirometra asiana, but not S. erinaceieuropaei, coexist in Japan [22,23].…”
mentioning
confidence: 99%
“…The infestation due to adult worms is asymptomatic in most cases; however, anorexia, diarrhea, and malnutrition are occasionally observed in companion animals, and intestinal obstruction may be caused in more severe infections [12]. Extensive studies of Spirometra infections have been performed in companion animals and wildlife in Japan and the etiological agents have been identified as Spirometra erinacei [1,16] or Spirometra erinaceieuropaei [3][4][5]7,11,[13][14][15]17,[18][19][20][21] based on the morphology of adult worms and eggs found. Molecular studies have recently revealed that two other species, Spirometra mansoni and Spirometra asiana, but not S. erinaceieuropaei, coexist in Japan [22,23].…”
mentioning
confidence: 99%